Long-Term Follow-Up after Surgery for Congenital and Developmental Cataracts. (3rd May 2016) - Magli, Adriano; Forte, Raimondo; Carelli, Roberta; Magli, Giulia; Esposito, Francesca; Torre, Angelo
Abstract: Purpose : To evaluate long-term functional outcomes after surgery for congenital and developmental cataracts. Methods : In this retrospective interventional study, patients with congenital and developmental cataracts observed from 1996 to 2013 were included. Traumatic cataracts and cataracts secondary to other pathologies were excluded from the study. Minimum follow-up for inclusion was five years. Results : We included 117 patients operated on for congenital cataracts (58 females and 59 males, mean age 0.59 ± 0.2 years, 160 eyes) and 73 patients operated on for developmental cataracts (32 females and 41 males, mean age 6.63 ± 0.7 years, 121 eyes). Mean postsurgical follow-up was 9.26 ± 1.3 years (range, 5–14 years). After surgery for developmental cataracts, both distance and near BCVA were greater ( p = 0.001), as was the presence of binocular vision ( p = 0.001), while incidence of strabismus and myopic shift was lower ( p = 0.001 and p = 0.02, respectively). Conclusion : Postsurgical data showed better functional outcomes in developmental cataracts when compared to congenital cataracts.